PENDETEKSI ARAH DATANG SINYAL UNTUK APLIKASI MONITORING FREKUENSI - Winala, Isra Putri; Degit Refniawan; Rayhan Almahdy; Edwar; Levy Olivia Nur (TEKTRIKA, 2024)
In a world that continues to grow rapidly, technological developments present new challenges, especially in terms of signal detection and control. The presence of unauthorized foreign signals especially at radio frequencies poses a serious threat to the stability of communications, especially in the field of aviation, radio frequency signal interference can threaten and endanger communications. For example, effective communication between air traffic controllers and pilots is essential. However, overlapping frequencies and illegal radio signals can disrupt such communication and threaten flight safety. Software Defined Radio (SDR) technology is an appropriate solution to enable adaptive frequency adjustments and detect the direction of incoming signals more effectively using GNU Radio. In the test using RTL-SDR, 2 test methods were carried out with a frequency of 145.525 Mhz. Tests were carried out using a dipole antenna with 2 antenna tilt methods, namely 90 and 135 °. From the test results, the dipole antenna with a 135° tilt has better accuracy than the dipole antenna with a 90° tilt.